Sale and Purchase Twitter Username According to Consumer Protection Law and Sharia Contract Law - Diana Ali Miftah (Fakultas Syariah Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
The advancement of technology and information encourages the emergence of various kinds of social media platforms that can be means of transactions between humans in various ways. One of which is sale and purchase usernames twitter. The type of research used is normative juridical research In the legal aspect of the sharia contract law and consumer protection law, the username also does not fulfill several elements including the object being traded must be clear and can be handed over, while username is an object that does not have a physical form to be handed over so that transactions like this are considered invalid and contain elements of gharar that can lead to problems in the future.